Evaluation of the quality and shelf-life of cayenne (Capsicum spp.). (June 2021) - Casquete, Rocío; Velazquez, Rocío; Hernandez, Alejandro; de Guia Cordoba, María; Aranda, Emilio; Bartolome, Teresa; Martin, Alberto
Abstract: A genetic characterization of 13 species of cayenne provided by Spanish milling industries was performed, and their colour, pungency and antioxidant properties were evaluated. Colour parameters (carotenoids, reflected and extractable colour), capsaicinoids, total phenolic compounds and antioxidant activity by the 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging method and 2, 2′-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) were determined in the cayenne samples, and the stability of cayenne properties was determined after exposure to UV light. Genetic characterization using different barcode markers (26S large subunit of rDNA, internal transcribed spacer 2, rbcL gene and matK gene) revealed close relationships among samples. However, notable differences were found for most of the quality parameters studied. Specifically, colour parameters were the most important traits for the discrimination of different samples. Samples with high colour quality presented 989.9 μg of capsanthin/g of dry matter, 104.8 ASTA units and 26.6 units in the a* coordinate of the CIELAB space. In contrast, the lowest-quality sample presented 582.7 μg of capsanthin/g of dry matter, 21.1 ASTA units and 15.4 units in the a* coordinate. DPPH and ABTS values ranged from 73.8 to 161.8 and from 217.1 to 325.7 mg Trolox/100 g, respectively. Pungency was highly variable among samples, with values ranging between 68.2 and 751.9 μg of capsaicin/g and 38.7 and 273.5 μg of dihidrocapsaicin/g. Principal component analysis indicated that capsaicinoids and total phenolic compounds are the best indices to determine the antioxidant activity of cayenne, which is highly correlated with the stability of colour and pungency. According to these findings, the desirable technological qualities and the longest shelf-life of cayenne are associated with a high content of capsaicinoids and phenolic compounds, which guarantee good colour stability and pungency associated with high antioxidant activity. Highlights: Pungency and colour are the main factors contributing to cayenne quality. Colour parameters, capsaicinoids and antioxidants were determined in cayenne samples. The stability of cayenne properties was determined after exposure to UV light. Capsaicinoids were the best indices to determine antioxidant activity of cayenne. Capsaicinoids are highly correlated with the stability of colour and pungency.